2001
DOI: 10.1103/physreve.63.021903
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of electroencephalographic spectra from neurophysiology

Abstract: A recent neurophysical model of propagation of electrical waves in the cortex is extended to include a physiologically motivated subcortical feedback loop via the thalamus. The electroencephalographic spectrum when the system is driven by white noise is then calculated analytically in terms of physiological parameters, including the effects of filtering of signals by the cerebrospinal fluid, skull, and scalp. The spectral power at low frequencies is found to vary as f(-1) when awake and f(-3) when asleep, with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

30
434
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 328 publications
(464 citation statements)
references
References 36 publications
30
434
0
Order By: Relevance
“…We have shown that neural mass models (David and Friston, 2003;Jansen and Rit, 1995;Lopes da Silva et al, 1997;Nunez, 1974;Rennie et al, 2002;Robinson et al, 2001;Stam et al, 1999;Suffczynski et al, 2001;Valdes et al, 1999;Wendling et al, 2002) can reproduce a large variety of MEG/EEG signal characteristics. The potential advantage they afford, in comparison to standard data analysis, is their ability to pinpoint specific neuronal mechanisms underlying normal or pathological activity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have shown that neural mass models (David and Friston, 2003;Jansen and Rit, 1995;Lopes da Silva et al, 1997;Nunez, 1974;Rennie et al, 2002;Robinson et al, 2001;Stam et al, 1999;Suffczynski et al, 2001;Valdes et al, 1999;Wendling et al, 2002) can reproduce a large variety of MEG/EEG signal characteristics. The potential advantage they afford, in comparison to standard data analysis, is their ability to pinpoint specific neuronal mechanisms underlying normal or pathological activity.…”
Section: Resultsmentioning
confidence: 99%
“…This means that MEG/EEG observation models rely upon simplifying assumptions and empirical priors (David and Friston, 2003;Freeman, 1978;Lopes da Silva et al, 1974;Robinson et al, 2001;Stam et al, 1999;Valdes et al, 1999;Van Rotterdam et al, 1982;Wendling et al, 2000). The primary aim of this paper is to describe a candidate forward model and establish its face validity.…”
Section: Neural Mass Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unless otherwise noted, we use the parameter values as listed in Appendix for numerical simulations. These values result from physiological experiments, and can be found in previous studies (Breakspear et al 2006;Chen et al 2014;Robinson et al 1998Robinson et al , 2001Robinson et al , 2003. At the same time, some parameter values are slightly adjusted to generate stable SWDs oscillation in corticothalamic circuit.…”
Section: Model Descriptionmentioning
confidence: 91%
“…Instead, it considers responses that are pooled across a group of cells. Dynamics of such models have been discussed by several authors (David and Friston 2003;Freeman 1975;Jansen and Rit 1995;Jirsa and Haken 1997;Nunez and Srinivasan 2006;Robinson et al 1997Robinson et al , 1998Robinson et al , 2001Rennie et al 2000). Although these models incorporate a nonlinear response function similar to the one in Eq.…”
Section: Gain and Threshold Modulationmentioning
confidence: 99%